2021
DOI: 10.1101/2021.10.01.21264409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health and Time Management Behavior among Students During COVID-19 Pandemic: Towards Persuasive Technology Design

Abstract: The study explored the impact of the COVID-19 pandemic on students' mental health in higher education while capturing their perceptions and attitudes towards time management. The aim was to examine relationships between stress, anxiety, and specific time management related factors. Considering possible differences between genders and degree levels, we developed five structural equation models (SEMs) to delineate these relationships. Results of a large-scale study of 502 participants show that students suffered… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Research has suggested that the effectiveness of persuasive strategies and the resulting intervention may vary across problem domains [43,44]. Research has also shown that the COVID-19 and associated precautionary measures took a toll on people's mental health [45] and games provided "dreamlands for the players to temporally escape from the cruel reality" and "a perfect social platform to keep social interaction with others to get rid of the loneliness" [46]. Therefore, this study focuses on designing and evaluating COVID-Pacman-C, a competition-based persuasive game for creating awareness motivating people to adhere to the COVID-19 precautionary measures.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Research has suggested that the effectiveness of persuasive strategies and the resulting intervention may vary across problem domains [43,44]. Research has also shown that the COVID-19 and associated precautionary measures took a toll on people's mental health [45] and games provided "dreamlands for the players to temporally escape from the cruel reality" and "a perfect social platform to keep social interaction with others to get rid of the loneliness" [46]. Therefore, this study focuses on designing and evaluating COVID-Pacman-C, a competition-based persuasive game for creating awareness motivating people to adhere to the COVID-19 precautionary measures.…”
Section: Background and Related Workmentioning
confidence: 99%
“…COVID-19 has swept the globe, forcing half of the world's population to close down by April 2020 [1], and the impact of this pandemic can be observed throughout many industries, including education [2][3][4][5][6][7]. Since the outbreak of this coronavirus, containment measures have been taken quickly by numerous countries in order to limit community transmission, with a view to bringing the disease under control gradually [8].…”
Section: Introductionmentioning
confidence: 99%